The perfect meal : the multisensory science of food and dining - Spence, Charles; Piqueras-Fiszman, Betina; Blumenthal, Heston (Chichester, West Sussex, UK : Wiley Blackwell, 2014)
' The authors of The Perfect Meal examine all of the elements that contribute to the diner's experience of a meal (primarily at a restaurant) and investigate how each of the diner's senses contributes to their overall multisensory experience. The principal focus of the book is not on flavor perception, but on all of the non-food and beverage factors that have been shown to influence the diner's overall experience.Examples are: the colour of the plate (visual) the shape of the glass (visual/tactile) the names used to describe the dishes (cognitive) the background music playing inside the restaurant (aural)Novel approaches to understanding the diner's experience in the restaurant setting are explored from the perspectives of decision neuroscience, marketing, design, and psychology'--
'The first book dedicated to the sensory science behind'eating out', considering every sensation involved in the dining experience'--
Includes bibliographical references and index.
Keywords: Gastronomy; Dinners and dining; Food -- Sensory evaluation; Senses and sensation; Intersensory effects